100 questions (and answers) about qualitative research - Given, Lisa M. (Thousand Oaks, California : SAGE, 2016)
Exploring 100 key questions (and answers) on the nature and practice of qualitative inquiry, this unique book addresses the practical decisions that researchers must make in their work, from the design of the study, through ethics approval, implementation, and writing. The book's quick-scan, question-and-answer format makes it ideal as a supplementary text or as a ready reference for graduate students preparing for comprehensive exams and writing research proposals, undergraduates in affiliated programs who will not be taking a primary course in qualitative research methods, and researchers working across a wide range of disciplines in academic or practice environments. Book jacket.
Includes index.
Keywords: Qualitative research -- Methodology; Social sciences -- Research -- Methodology